An Action Research Study on the Pronunciation Challenges Faced by Doteli Students - Bist, Nar Bahadur; Bohara, Nirajan (International Research Journal of MMC, 2026)
This qualitative action research study focused on identifying the pronunciation difficulties experienced by Doteli-speaking students in grades 8-10 in Doti, as well as examining how collaborative multimodal instructional strategies can help improve their English pronunciation. We used purposive sampling methods for data collection, with primary data including classroom observations, student work samples, and reflections, while secondary data consisted of relevant literature concerning second language acquisition. The qualitative thematic analysis identified three barriers to improving English pronunciation for the participating students: First language interference, limited resources available within the classroom, and lack of motivation due to limited exposure to English outside of the classroom. After the implementation of collaborative activities such as pronunciation modelling techniques, vocabulary puzzles, and phonetic reinforcement, there was an increase in correct pronunciation, fluency, and confidence level. The results of this study indicate that collaborative multimodal strategies and supportive learning environments help reduce pronunciation errors among non-native speakers of English, thereby providing practical instructional approaches for educators working in low-resource contexts.